Data transparency and reproducibility in health research: bridging the gap for early-career researchers - Bhakta, Sanjib; Xie, Jianping; Pea, Federico; Gillespie, Stephen H. (Frontiers in Antibiotics, 2025)
In the evolving and interdisciplinary landscape of health and disease research, data transparency and reproducibility are increasingly recognised as essential for maintaining scientific integrity and trust. This article invites early-career researchers (ECRs) to engage critically with these principles while navigating the pressures of academic progression, publication demands, and career development. It examines the challenges ECRs face in maintaining reproducible practices and underscores the need for institutional support, inclusive training, and mentorship across all stages of the research career. Drawing on global initiatives and case studies, the article advocates for a more collaborative, diverse, and mentally healthy research culture. It also highlights alternative career pathways beyond academia, empowering ECRs to explore opportunities in industry, government, and non-governmental organisations. By integrating transparency with values such as team science, responsible metrics, and researcher wellbeing, this article reflects the ethos of the new generation of scientists and offers a timely call for systemic change and collective action to strengthen the future of research culture.